Correlates of Hepatitis B Virus and HIV Knowledge Among Gay and Bisexual Homeless Young Adults in Hollywood. (January 2013) - Nyamathi, Adeline; Salem, Benissa; Reback, Cathy J.; Shoptaw, Steven; Branson, Catherine M.; Idemundia, Faith E.; Kennedy, Barbara; Khalilifard, Farinaz; Marfisee, Mary; Liu, Yihang
Homeless gay and bisexual (G/B) young men have multiple risk factors that increase their risk of contracting hepatitis B virus (HBV) and human immunodeficiency virus (HIV). This study used baseline information from structured instruments to assess correlates of knowledge to HIV and HBV infection from 267 young (18-39 year old) G/B active methamphetamine, cocaine, and crack-using homeless men enrolled in a longitudinal trial. The study is designed to reduce drug use and improve knowledge of hepatitis and HIV/AIDS in a community center in Hollywood, California. Regression modeling revealed that previous hepatitis education delivered to G/B men was associated with higher levels of HIV/AIDS and hepatitis knowledge. Moreover, higher HIV/AIDS knowledge was associated with combining sex and drinking alcohol. Associations with hepatitis B knowledge was found among G/B men who were engaging in sex while under the influence of marijuana, who were receiving support from non–drug users, and who had been homeless in the last 4 months. Although being informed about HIV/AIDS and hepatitis did not preclude risky sexual and drug use behavior, knowledge about the dangers of concurrent sex with substance use is important. As higher levels of knowledge of hepatitis was associated with more moderate drug use, early access to testing and teaching harm reduction strategies remain critical to reduce exposure and infection of HBV and HIV in this population.